Implantless osteosynthesis of lateral end of clavicle fractures using autologous palmaris longus tendon graft for coracoclavicular ligament reconstruction - Kumar, Debangshu; Khalkho, Amrit; Aziz, Tarikh A.; Hossain, Nazir (International Surgery Journal, 2023)
Background: Lateral end clavicle fractures require operative management because of significant displacing forces of trapezius, sternocleidomastoid and weight of the arm. Coracoclavicular ligaments are usually torn hampering vertical stability. Currently used implants for osteosynthesis are associated with implant impingement on acromion, poor purchase of lateral fragment and implant cut-out. There is a lack of consensus regarding ideal treatment of these fractures. Methods: 31 patients with lateral clavicle fracture who were admitted from May 2019 to August 2022 were enrolled in this study and underwent coracoclavicular ligament reconstruction using ipsilateral palmaris longus graft looped around coracoid and tied over clavicle to hold it reduced. Patients were assessed for pain, shoulder range of motion and functional outcome with 6-month follow-up. Results: All patients showed radiological union with good to excellent outcome in 79.3% patients and mean abduction of 157⁰. Mean duration of surgery was 104 minutes (SD±12.118) and 10.3% patients showed shoulder stiffness. Conclusions: The study shows encouraging prospect in purely biological osteosynthesis with functional outcome at par with other methods of fixation while avoiding implant related complications.